THE ROLE OF AGRARIAN REFORM IN RESOLUTION OF TENURIAL CONFLICTS IN THE LEGISLATION AREA - Rifal Al Ikhsan; Farahwati; Rezky Robiatul Aisyiah Ismail; Heribertus Richard Charsarino (Awang Long Law Review, 2025)
Land ownership and control disputes in Indonesia are complex legal issues, rooted in unequal land distribution, overlapping laws and regulations, and minimal recognition of the rights of indigenous peoples and local communities. From the colonial period to the reform era, agrarian policies in Indonesia have often created legal uncertainty, particularly regarding the designation of state forest areas and conservation that ignore community customary rights. Agrarian reform exists as a strategic instrument to address structural inequalities, resolve land disputes, and realize social justice as mandated by MPR Decree No. IX/MPR-RI/2001 and UUPA No. 5 of 1960. This study uses a normative method by examining various laws and regulations, doctrines, and legal theories related to agrarian matters and the resolution of tenurial conflicts. The results show that the effectiveness of agrarian reform in resolving tenurial conflicts is highly dependent on the harmonization of cross-sectoral regulations, the strengthening of state institutions such as the Agrarian Reform Task Force (GTRA) and the ATR/BPN, and the recognition of indigenous peoples' rights. The theoretical approach of national agrarian law, social justice, and a holistic legal system emphasizes that agrarian reform is not merely land redistribution, but also a process of legal renewal and agrarian governance that is just, participatory, and sustainable. Therefore, agrarian reform must be positioned as the primary legal instrument in resolving tenure conflicts, leading to legal certainty and social justice for all levels of society.